2006
DOI: 10.1104/pp.106.085878
|View full text |Cite
|
Sign up to set email alerts
|

Dual Temporal Role of Plastid Sigma Factor 6 in Arabidopsis Development

Abstract: Plants contain nuclear-coded sigma factors for initiation of chloroplast transcription. The in vivo function of individual members of the sigma gene family has become increasingly accessible by knockout and complementation strategies. Here we have investigated plastid gene expression in an Arabidopsis (Arabidopsis thaliana) mutant with a defective gene for sigma factor 6. RNA gel-blot hybridization and real-time reverse transcription polymerase chain reaction together indicate that this factor has a dual devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
79
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 48 publications
3
79
0
Order By: Relevance
“…NEP promoters are more active in the youngest, nongreen tissues early in leaf development, while PEP increases its activity during the maturation of chloroplasts (Allison et al, 1996;Hajdukiewicz et al, 1997). The complexity of promoter specificity and chloroplast transcription initiated by PEP is further increased by multiple nucleus-encoded s factors, whose expression is spatially and temporally regulated by environmental cues (Hess and Börner, 1999;Allison, 2000;Shiina et al, 2005;Loschelder et al, 2006). There are six chloroplast s factors (SIG1-SIG6) in Arabidopsis (Arabidopsis thaliana).…”
mentioning
confidence: 99%
“…NEP promoters are more active in the youngest, nongreen tissues early in leaf development, while PEP increases its activity during the maturation of chloroplasts (Allison et al, 1996;Hajdukiewicz et al, 1997). The complexity of promoter specificity and chloroplast transcription initiated by PEP is further increased by multiple nucleus-encoded s factors, whose expression is spatially and temporally regulated by environmental cues (Hess and Börner, 1999;Allison, 2000;Shiina et al, 2005;Loschelder et al, 2006). There are six chloroplast s factors (SIG1-SIG6) in Arabidopsis (Arabidopsis thaliana).…”
mentioning
confidence: 99%
“…The Arabidopsis genome encodes six plastidlocalized s-factors (SIGs; SIG1-SIG6) that are clustered into the same superfamily of s 70 and implement the same function as those in bacteria (Gruber and Gross, 2003;Lysenko, 2007). Physiological and genetic evidence revealed that different s-factors function redundantly and specifically to regulate plastid gene expression in Arabidopsis (Kanamaru et al, 2001;Privat et al, 2003;Yao et al, 2003;Nagashima et al, 2004;Tsunoyama et al, 2004;Favory et al, 2005;Ishizaki et al, 2005;Loschelder et al, 2006;Zghidi et al, 2007). For example, loss of function of SIG2 or SIG6 resulted in slow chloroplast development because of inhibition of plastid gene expression, and the sig2 sig6 double mutant showed a very severe defect in chloroplast development and was unable to grow in nature (Shirano et al, 2000;Hanaoka et al, 2003;Ishizaki et al, 2005;Woodson et al, 2012).…”
mentioning
confidence: 99%
“…This gene is transcribed by the plastid-encoded plastid RNA polymerase (PEP) which functions in the expression of the other genes related to photosynthesis. The specificity for target genes and the spatial-temporal regulation of PEP-mediated transcription are regulated by nuclear-encoded sigma-like transcription factors (SIGs) (Isono et al 1997;Kanamaru and Tanaka 2004;Tsunoyama et al 2004;Favory et al 2005;Loschelder et al 2006;Tozawa et al 2007;Zghidi et al 2007). AtSIG6, which is one of the six SIGs identified in Arabidopsis, is involved in rbcL gene expression during the early developmental stage when the biosynthesis of RuBisCO is most active (Ishigaki et al 2005).…”
Section: Gene Expression Of Nuclear-and Chloroplast-encoded Subunits mentioning
confidence: 99%